Morphodynamic processes in the coastal zone of the Caspian Sea (Gobustan, Azerbaijan): distribution and risks of manifestation - Tarikhazer, Stara (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2025)
Problem statement. This study aims to analyze hazardous morphogenetic processes associated with the active development of tourism and recreational activities in the southeastern part of the Greater Caucasus. The importance of this problem lies in the fact that the creation of a National Geopark with internationally significant is planned in the territory of Gobustan.Purpose - The study area – Gobustan, as an integral part of the mobile epigeosynclinal orogenetic zone, is characterised by a rather complex geological and geomorphological structure. Located in the southeastern subsidence of the Greater Caucasus, near the Caspian Sea and representing part of the geosynclinal folded area of the same name, it is very promising in terms of tourism and recreation. Due to the significant diversity of the geological formations widespread, the tectonic structure, and the differentiated nature of intense neotectonic movements, the landforms of the territory are characterised by dangerous morphodynamic processes (earthquakes of magnitude 7-8, mud volcano eruptions, landslides, mudflows, ravines, etc.).Research method. Based on our field geological and geomorphological studies, cartographic material, and the use of aerial photographs (ACS) from 1996, 2000-2020 at a scale of 1:60,000, the morphogenetic tension areas of Gobustan have been revealed for the first time. At the same time, the most dangerous processes (landslides, mudflows), as well as the morphometry of the landform (vertical and horizontal dismemberment, steepness and exposure of slopes) were highlighted.Research results. Territories with characteristic geological and geomorphological conditions, where morphogenetic processes differ in the nature of manifestation and degree of tension (weakly, moderately and tense): the area of a slightly tense territory (I b.) is 298.81 hectares (53.4%), the area of medium-stressed territory (II b.) - 217.67 hectares (38.9%), the area of the tense territory (III b.) - 43 hectares (7.7%). As a result of a detailed study of the collected information and data, the study area according to the nature of the surface and elevations, as well as under the condition of morphometric tension and taking into account varying degrees of morphogenetic danger, the territory of Gobustan was zoned according to the distribution of morphogenetic processes and landforms: the middle mountains (with absolute heights up to 1300-1700 m), the lowlands (with absolute heights up to 800-1000 m) and the lowland zone (with absolute heights up to 50-100 m). In these zones, some morphogenetic processes pose a real threat to the development of recreational and tourism activities that are exclusively dependent on the landforms, and the construction of the corresponding infrastructure.Conclusion. The research results will make it possible to use the data obtained to develop a Program for the safe and sustainable functioning and development of the geosystems of Azerbaijan for recreational and tourism development. The relevance of this work also lies in the fact that it is planned to create a National Geopark with internationally significant in the territory of Gobustan.